2020
DOI: 10.1111/1556-4029.14539
|View full text |Cite
|
Sign up to set email alerts
|

Responsive Aggression Regulation Therapy (Re‐ART) Improves Executive Functioning in Adolescents and Young Adults with Severe Aggression Problems: A Pilot Study

Abstract: This pilot study (N = 25) compared the effects of a short, four-month version of Responsive Aggression Regulation Therapy Outpatient (Re-ART Compact) and the entire, ten-month intervention (Re-ART Complete) on specific executive functioning (EF) and the risk of violent recidivism in adolescents and young adults (13-23 years). Re-ART is a cognitive behavioral-based intervention for adolescents and young adults with severe aggression problems. The Re-ART Compact and Re-ART Complete groups were comparable on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Yet studies that employ such laboratory interventions often produce null results, whether the approach takes the form of training exercises (Beames et al., in press), psychostimulants such as caffeine (Denson et al., 2012), or brain stimulation (Dambacher et al., 2015). Outside of the lab – in classrooms, clinics, mobile phone applications, hospitals, and out in communities – many interventions seek to reduce real‐world violence in a similar way, by improving self‐control skills (e.g., Denson, 2015; Kip et al., 2021; Schippers et al., 2020; see). I do not call for a stop to such interventions.…”
Section: Implications For Aggression‐reducing Interventionsmentioning
confidence: 99%
“…Yet studies that employ such laboratory interventions often produce null results, whether the approach takes the form of training exercises (Beames et al., in press), psychostimulants such as caffeine (Denson et al., 2012), or brain stimulation (Dambacher et al., 2015). Outside of the lab – in classrooms, clinics, mobile phone applications, hospitals, and out in communities – many interventions seek to reduce real‐world violence in a similar way, by improving self‐control skills (e.g., Denson, 2015; Kip et al., 2021; Schippers et al., 2020; see). I do not call for a stop to such interventions.…”
Section: Implications For Aggression‐reducing Interventionsmentioning
confidence: 99%
“…Contrary to expectations, this study found no difference in treatment effect between a combined form of treatment (other than parent involvement) or treatment solely with mindfulness. Looking at the principles of RNR (Bonta & Andrews, 2017), it was expected that combined treatment would be more effective (in the long term) in reducing externalizing problem behavior and the risk of criminal recidivism (Bonta & Andrews, 2017), because of the possibility to focus the treatment on various critical domains or risk factors (e.g., Schippers et al, 2020). A possible explanation for the result of this meta-analysis could be that the included studies mainly examined the effect at the end of treatment, yielding insufficient information on the long-term effects of mindfulness-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Yet studies that employ such laboratory interventions often produce null results, whether the approach takes the form of training exercises (Beames et al, in press), psychostimulants such as caffeine , or brain stimulation (Dambacher et al, 2015). Outside of the lab ---in classrooms, clinics, mobile phone applications, hospitals, and out in communities ---many interventions are seeking to reduce real-world violence in a similar way, by improving the self-control skills of people and many of these are effective (e.g., Kip et al, 2021;Schippers et al, 2020;see Denson, 2015). I do not call for a stop to such interventions.…”
Section: Implications For Aggression-reducing Interventionsmentioning
confidence: 99%